2017
DOI: 10.17140/whoj-3-115
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Fatigue in Female Nurses Employed in Hospitals

Abstract: Background: Fatigue is the inability to maintain the required stamina in work capacity with consequences affecting occupational performance, health, and safety. Women are often more exposed to the risk of fatigue because they tend to be multitaskers. The present survey is aimed at determining the perceived fatigue in female nurses employed in hospitals and identifying the individual and occupational factors affecting it. Methods: This survey was conducted on 270 female nurses. The sample was selected using mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Moreover, the impact of demographic as well as occupational factors on level of fatigue is in line with other research findings [30,31]. Last but not least, this study had some limitations due to its small sample.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the impact of demographic as well as occupational factors on level of fatigue is in line with other research findings [30,31]. Last but not least, this study had some limitations due to its small sample.…”
Section: Discussionsupporting
confidence: 89%
“…Singles showed higher rates of total fatigue, while widowed indicated greater satisfaction with working conditions, salary and the organization. These findings reinforce the literature that highlights the impact of marital status and family support on employee fatigue (Fradelos et al, 2014;Pourmovahed & Nasiriani, 2016). Also, laboratory/research staff displayed higher rates of physical, mental and total fatigue.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, through Harkin and Melby's (2014) research into emergency department nurses and clinical nurses, work-related factors, gender, age, marital status, and the number of hours worked per week were significant in terms of their association with occupational fatigue. On the other hand, a recent study on fatigue in female nurses showed that they had high rates of fatigue, while it appeared that work fatigue was affected by their employment status, age, husband support and work experience, but not by their marital status, official position, work shift, having a suckling or having a second job (Pourmovahed & Nasiriani, 2016).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Work-related factors and personal factors of gender, age, marital status and number of hours worked per week were significant (p<.05) in their association with occupational fatigue. In the research conducted by Zahra Pourmovahed and KhadijehNasiriani [10] regarding the perception of fatigue in female nurses, the total score of fatigue was 30.78±7.90. There was a statistically significant difference between employment status (p = 0.01), spousal support (p = 0.00), age (p = 0.008) and work experience (p = 0.02) on one side, and fatigue.…”
Section: Introductionmentioning
confidence: 99%